Enseñanza de idiomas en escuelas de medicina humana de Perú - Arce-Villalobos, Laura Rosa (2017)
Abstract Introduction: Medical schools in Latin America should ensure that their graduates know certain languages besides Spanish, however, little has been described on the subject in Peru. Objective: To describe the characteristics of second language teaching in medical schools of Peru. Materials and methods: Cross-sectional analytical study carried out in August 2015 in human medicine schools of Peru. At least two students from each school were contacted, and variables of interest were collected. Subsequently, the collected data were compared and analyzed using the STATA v13 program. Results: Data were obtained from 36 medical schools. All of them offered at least one English course -which was mandatory in 25 schools-, while 6 schools offered a Quechua course. The schools with compulsory English courses were located mostly outside Lima and began to operate before 1999. Many of the public schools offered compulsory English courses that include seminars, practices and workshops, which cannot be validated and are offered by the school. Conclusion: Few schools offered at least one Quechua course, although all of them offered English courses.